Optimalisasi Fungsi Laboratorium IPAMelalui Kegiatan Praktikum Di SMP Negeri 4 Sinjai Timur Kabupaten Sinjai - Muliana, Muliana; Wahyuni, Sri; Erwing, Erwing (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
ABSTRACK. This study aims to determine the optimization of the science laboratory function through practical activities for class VIII students of SMP Negeri 4 Sinjai Timur, Sinjai Regency. The type of research used in this research is descriptive qualitative research which will describe the results of measurements on the optimization of the functions of the science laboratory through practicum. The population of this study were all students of class VIII A of SMP Negeri 4 Sinjai Timur, Sinjai Regency, totaling 31 people with a distribution of 11 males and 20 females. The research instruments used were questionnaires, observations and document studies. The data obtained were then analyzed using data processing and data analysis. Based on data analysis that research on how to optimize the function of the science laboratory through student practicum activities, it was concluded that the implementation aspect of biology practicum learning showed that on average each questionnaire item given to students gave an answer category above 50% with categories strongly agree and agree and at aspects of laboratory utilization based on the questionnaires that researchers have distributed regarding optimizing the functions of the science laboratory through practical activities for class VIII students of SMP Negeri 4 Sinjai Timur on average give answers strongly agree and agree with a percentage above 50%.